The value of ultrasound elastography in differentiation of malignancy in thyroid nodules - (:unkn) unknown (ELSEVIER SCIENCE INC, 2014)
We aimed to determine the value of ultrasound elastography (US-E) using carotid artery pulsation in differentiation of malignant and benign thyroid nodules. One hundred ten nodules were evaluated by US-E, and stiffness scores were compared to biopsy results. When cutoff for malignancy was determined as score 4, sensitivity, specificity, positive predictive value, and negative predictive value were 100%, 95%, 40%, and 100%, respectively. We suggest fine needle aspiration biopsy to be performed in all score 4 nodules, while biopsy may be unnecessary in score 1 nodules. Benign biopsy result in a score 4 nodule should suggest radiologicalpathological disagreement, and repeat biopsy should be recommended. (c) 2014 Elsevier Inc. All rights reserved.
Keywords: Elastography; Fine needle aspiration biopsy; Nodule; Thyroid gland; Ultrasound; FINE-NEEDLE-ASPIRATION; CAROTID-ARTERY PULSATION; REAL-TIME ELASTOGRAPHY; US-ELASTOGRAPHY; PREDICTING MALIGNANCY; BIOLOGICAL TISSUES; BREAST-LESIONS; DIAGNOSIS; BIOPSY; BENIGN